Modeling and performance analysis of an adaptive PID speed controller for the BLDC Motor - Mahmud, Md; Motakabber, S. M. A.; Zahirul Alam, A. H. M.; Nordin, Anis Nurashikin; Ahasan Habib, A. K.M. (The Science and Information (SAI) Organization Limited., 2020)
Brushless Direct Current (BLDC) motor is themost popular useable motor for automation and industry. For good performance of the BLDC motor hunger driving circuit but the driving circuit is costly, complex control mechanism, various parameter dependency and low torque. The Proportional Integral (PI), Proportional Integral Derivative (PID), fuzzy logic, adaptive, Quantity Feedback Theory (QFT), Pulse Width Modulation (PWM) controller are the common types of control method existing for the BLDC motor. This research explores some well-working experiments and identified the PID controller as far more applicable controller. For well efficacious and useful in getting satisfied control performance if the adaptability is implemented. This research proposed a combined method using PID and PID auto tuner, having the ability to improve the system adaptability, given the method named as adaptive PID controller. To verify the performance, MATLAB simulation platform was used, and a benchmark system was developed based on the actual BLDC motor parameters, auxiliary systems, and mathematically solved parameters. All work has done by using MATLAB/Simulink.